Comparação de fontes de ureia de lenta liberação sobre a degradação in vitro do capim King grass (Pennisetum purpureum x Pennisetum typhoides) (2015)
ABSTRACT: The aim of this study was to evaluate the effect of two sources of slow release urea on in vitro dry matter degradation of King grass pasture. The treatments were evaluated by the in vitro gas production technique. SU = treatment without the addition of urea; UP = treatment with urea covered with biodegradable polymer; UCC = treatment with protected urea calcium carbonate microcapsules; UCOM = treatment with commercial urea. The variables studied were: dry matter degradation, ammonia concentration and methane production. Data were analyzed using a mixed linear model considering as a random effect the donor animal of inoculum and as fixed effects the treatments and the incubation time. The treatments were compared by Tukey test (p <0.05). The treatments with slow-release urea (UP and UCC) exhibited higher dry matter degradation (p <0.05) than the SU and UCOM treatments. The UCC treatment showed a greater degree of protection by a minor releasing of ammonia (40% less than the treatment with urea commercial) (p <0.05). The UCC treatment showed lower methane production when compared with the treatment with commercial urea (UCOM). This fact showing that the energy was used for microbial growth before than for methane production. The slow-release urea sources were more efficient than the commercial urea to achieve further degradation of dry matter and improve the use of nitrogen. Furthermore, these sources reduced the methane and ammonia production, potential environmental pollutants.